Rebellious Wallflowers and Queer Tangueras The Rise of Female Leaders in Buenos Aires' Tango Scene - McMains, Juliet (Edinburgh: Edinburgh University Press, 2018)
RESUMEN: This paper interrogates the history of same-sex dancing among women in Buenos Aires' tango scene, focusing on its increasing visibility since 2005. Two overlapping communities of women are invoked. Queer tangueras are queer-identified female tango dancers and their allies who dance tango in a way that attempts to de-link tango's two roles from gender. Rebellious wallflowers are women who practice, teach, perform, and dance with other women in predominantly straight environments. It is argued that the growing acceptance of same-sex dancing in Argentina is due to the confluence of four developments: 1) the rise of tango commerce, 2) innovations of tango nuevo, 3) changing laws and social norms around lesbian, gay, bisexual, and transgender rights, and 4) synergy between queer tango dancers and heterosexual women who are frustrated by the limits of tango's gender matrix. The author advocates for increased alliances between rebellious wallflowers and queer tangueras, who are often segregated from each other in Buenos Aires' commercial tango industry. PALABRAS CLAVE: Argentine tango, queer tango, Buenos Aires, same-sex dancing, rebellious wallflowers, gender roles.
In Memory of Ivor Guest, Dance Historian Joint-Founder of the Society for Dance Research and of its Journal (14 April 1920 - 30 March 2018)